PROTOTIPE JENDELA KACA UNTUK RUANG BERJEMUR DALAM RANGKA MENINGKATKAN IMUNITAS TUBUH - Sri Kurniasih; I Made Joshua Pratama (Jurnal Arsitektur ARCADE, 2020)
The coronavirus outbreak is now a problem for the world community. Not only has the potential to interfere with health, the coronavirus often causes panic. In fighting the SARS-CoV virus that causes the Covid-19 pandemic, a qualified body defense is needed. Although some local governments implement quarantine policies to prevent people from being exposed to the risk of the Covid-19 virus, not all people can carry out quarantine at home because of work demands. Therefore, efforts are needed to increase endurance. In addition to workers who are required to continue working even though they have to be quarantined at home, the elderly and also children whose immune systems are still vulnerable or have decreased need to increase their immune system. The easiest way to increase body resistance is to bask in the sun. Sunbathing can be done directly outside the house and can be directly exposed to sunlight, but for some people whose body conditions are not as strong as young people, for example, the elderly, people with special needs, are vulnerable, suffer from dust allergies, and so on, this will cause new problems. So for some people who cannot go outside directly or who are less flexible, they still need sunlight for sunbathing. One way is to enter sunlight through the window openings in the house. This research was conducted with the main objective of creating a prototype or prototype window for the sunroom in the building to increase the body's immunity using the DiaLux software. The research method used in this study is a quantitative research method with an experimental approach. The stages of this research are in the form of; i) theoretical study, ii) data observation, iii) calculation, iv) window prototyping, v) analysis and synthesis, v) simulation, vi) research result generation and conclusion drawing. The result of this research is a prototype window for human sunbathing space which is expected to accommodate or provide human sunbathing space in increasing body immunity. The window prototype in the sunroom that most maximally includes natural light with a lighting intensity value of 8701 lx, namely prototype window 3 which is a window or opening on the roof of a building with dimensions of 1.20 m x 0.83 m. By providing a multifunctional sunbed, it can be an architectural solution to increase the body's immunity to prevent the outbreak of the Covid-19 virus.